UTILIZATION OF CLIMATE-SMART RICE PRODUCTION TECHNOLOGIES AMONG SMALLHOLDER FARMERS IN ABAKALIKI LOCAL GOVERNMENT AREA OF EBONYI STATE, NIGERIA - Agou, G. D.; Njoku, L. C.; Ankrumah, E.; Otude, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out in Abakaliki Local Government Area of Ebonyi state. The broad objective of the study was to assess utilization of climate-smart rice production technologies among smallholder rice farmers. The specific objectives were to: assess the utilization of climate smart rice production technologies and determine the factors influencing the utilization of climate-smart rice production technologies. Multistage sampling procedure was used to select 85 rice smallholder rice farmers. Questionnaire was used for data collection while frequency, percentage, mean and binary logistics were used for data analysis. The study found that 56.5% of the rice farmers were males, 42.4% were married, 38.8% had secondary education. More so, the findings revealed that 96.5% of the rice farmers utilized crop rotation, 94.1% used disease-resistant varieties, 91.8% used agroforestry, 90.6% made use of efficient fertilizer application and 90.6% efficient use of herbicides. The results also showed that source of credit was a factor influencing the utilization of climate-smart rice production technologies. Financial institutions should prioritize providing credit to farmers for investment in climate-smart rice production technologies that will boost yields and income.